Clinical Manifestation and Management of Terrestrial Animal Bites - Emma Hidayati Sasmito; Sawitri Sawitri (Faculty of Medicine, Universitas Airlangga, 2021)
Background: Terrestrial animal bites wounds are injuries caused by terrestrial animals' mouths and teeth. Aerobic and nonaerobic bacteria cause 30–60% of the secondary bacterial infections due to animal bites. Rabies is an infectious disease and it is the most dangerous viral infection caused by animal bites. Also, venomous animal bites can be fatal and cause death if not treated well. Purpose: To identify the clinical manifestation, first aid, and management of terrestrial animal bites to reduce morbidity and mortality. Review: Wounds and crush injuries caused by animal bites are prone to infection. Aerobic bacteria, such as Pasteurella multocida, Staphylococcus spp. (including methicillin–resistant Staphylococcus aureus (MRSA)), Capnocytophaga canimorsus, and Bartonella henselae, and anaerobic bacteria, such as Porphyromonas spp. are commonly found pathogens in animal bite wounds. Rabies, the most dangerous viral infection, occurs in wounds infected by the rabies virus. The virus enters the nerve tissue, multiplies, and spreads to the central nervous system. This can cause disability, and it is life-threatening. In snakebites, management of basic life support, transportation to the hospital, clinical assessment, and immediate resuscitation are the most important procedures. Conclusion: Animal bite wounds are injuries caused by animals' mouths and teeth. Dogs, cats, and snakes are terrestrial animals that most likely attack humans. Proper diagnosis, first aid, and comprehensive management are needed to reduce morbidity and mortality.